Effects of Certain Phospholipids on Plasminogen Activation and Plasmin Activity - Gerbeck, Claire; Koppel, J. L; Olwin, John H (Thrombosis and Haemostasis, 1962)
Crude and partially purified phospholipid preparations have been studied for their effects on a) the activation of purified human plasminogen by streptokinase and b) the activity of plasmin resulting from such activation. Plasmin activity has been measured as BAMe esterase, caseinolytic, and fibrinolytic activities.Plasmin BAMe esterase activity was significantly enhanced by phosphatidyl inositol and phosphatidyl serine but only slightly by phosphatidyl ethanolamine. Preparations of asolectin and cephalin, although not having any effect on plasmin BAMe esterase activity per se, did appear to increase plasminogen activation by streptokinase. None of the above-mentioned effects was observed when plasmin caseinolytic activity was measured. The phospholipid preparation having the greatest effect on plasmin BAMe esterase activity, phosphatidyl inositol, also exhibited an effect on plasmin fibrinolytic activity. With both BAMe esterase and fibrinolytic activities the effects produced by the phospholipid materials were concentration dependent and, in the case of fibrinolytic activity, increased concentrations beyond the optimum level resulted in a gradual diminution in activity and eventual inhibition.